2015
DOI: 10.3748/wjg.v21.i47.13352
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of symptomatic reflux episodes in Japanese proton pump inhibitor-refractory non-erosive reflux disease patients

Abstract: The proximal extent of weakly acidic liquid and mixed liquid-gas reflux is a major factor associated with reflux perception in SI-positive patients on proton pump inhibitor therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…A previous study demonstrated that proximal spread of weakly acid reflux determines the perception of reflux in GERD patients without apparent esophageal injury on PPI therapy [21, 22]. Then, we recently revealed that the proximal extent of weakly acidic reflux is critical to the perception of reflux in patients with nonerosive reflux disease despite the use of PPIs [23]. Thus, we hypothesized that an alternation in esophageal mucosal integrity by location could be associated with acid hypersensitivity, which causes reflux perception in the patients.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that proximal spread of weakly acid reflux determines the perception of reflux in GERD patients without apparent esophageal injury on PPI therapy [21, 22]. Then, we recently revealed that the proximal extent of weakly acidic reflux is critical to the perception of reflux in patients with nonerosive reflux disease despite the use of PPIs [23]. Thus, we hypothesized that an alternation in esophageal mucosal integrity by location could be associated with acid hypersensitivity, which causes reflux perception in the patients.…”
Section: Introductionmentioning
confidence: 99%
“…The PPI responsiveness in patients with NERD was reported to be < 60% [3]. Although the mechanisms of reflux perception remain unclear, patients with NERD have been reported to be more hyper-DOI: 10.1159/000500133 sensitive to visceral stimulation than those with ERD due to a reduced pain threshold [4][5][6]. Therefore, NERD is not just a mild form of ERD.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of combined multichannel intraluminal impedance and pH (MII-pH) monitoring made possible the detection of non-acidic and acidic refluxes [7]. Recent studies have demonstrated that weakly acidic reflux (reflux of pH 4-7) was the major cause of symptom occurrence in patients with PPI-refractory NERD who underwent PPI treatment [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 However, some authors believe that lack of clinical response after a 8-week course of PPI may be sufficient to define refractoriness for NERD. 7 , 8 Refractory NERD is often a therapeutic challenge. Indeed, in a systematic review, pooled rate of symptomatic response to PPI was 36.7% (95% confidence interval: 34.1–39.3) in NERD and 55.5% (95% confidence interval: 51.5–59.5) in erosive esophagitis.…”
mentioning
confidence: 99%